Rules of Origin in North-South Preferential Trade Agreements - Angeli, Marietta (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The study of trade agreements contains a knowledge gap in relation to Rules of Origin. In their simplest form, Rules of Origin are legal standards through which goods benefit from preferential market access and which prevent tariff fraud, but in practice they have mushroomed to create thousands of complex hurdles to preferential trade between developing and industrialised countries. In this study, the author fills this knowledge gap by analysing new data on the design, negotiation and impact of Rules of Origin on trade between developing and industrialised economies. Her conclusions show that a pragmatic reform of Rules of Origin in free trade agreements is both feasible and necessary.